The Predictive Validity of Machine Learning Models in the Classification and Treatment of Major Depressive Disorder: State of the Art and Future Directions - Ermers, Nick J.; Hagoort, Karin; Scheepers, Floortje E. (Frontiers in Psychiatry, 2020)
Major depressive disorder imposes a substantial disease burden worldwide, ranking as the third leading contributor to global disability. Despite its ubiquity, classifying and treating depression has proven troublesome. One argument put forward to explain this predicament is the heterogeneity of patients diagnosed with the disorder. Recently, many areas of daily life have witnessed the surge of machine learning techniques, computational approaches to elucidate complex patterns in large datasets, which can be employed to make predictions and detect relevant clusters. Due to the multidimensionality at play in the pathogenesis of depression, it is suggested that machine learning could contribute to improving classification and treatment. In this paper we investigated literature focusing on the use of machine learning models on datasets with clinical variables of patients with depression, to predict treatment outcomes or find more homogeneous subgroups. Identified studies are evaluated based on best practices in the field. We found 16 studies predicting outcomes and identifying clusters in patients with depression. The identified studies are mostly still in proof-of-concept phase, with small datasets, lack of external validation, and providing single performance metrics. Larger datasets, and models with similar variables present across these datasets, are needed to develop accurate and generalizeable models. We hypothesize that harnessing natural language processing to obtain data ‘hidden’ in clinical texts might prove useful in improving prediction models. Besides, researchers will need to focus on the conditions to implement these models to support psychiatrists in their decision-making. Only then we can enter the realm of precision psychiatry.